Akun Media Sosial Instagram @cegahstunting Sebagai Media Edukasi Stunting - De Putri, Sekar; Witarti, Denik Iswardani (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
Stunting is the number 1 nutritional problem in Indonesia which is still a problem and concern on a national scale. Deputy Minister of Health of the Republic of Indonesia Prof. Dr. Dante Saksono Harbuwono said the government is targeting stunting cases to fall by 14% by 2024. The central and regional governments have made various efforts to deal with stunting, so that several health workers have also carried out their duties in educating the public about stunting, one of which is Dr.dr. Brian Sriprahastuti, MPH who educates about preventing and handling stunting through the Instagram social media account @cegahstunting. This research uses a qualitative approach with descriptive analysis methods. Observations carried out by researchers were in the form of participant observation. The results of this research are that the Instagram account @cegahstunting is a social media account that actively provides educational content about how to prevent and treat stunting. The presence of the @cegahstunting account can be a reference medium for providing educational information about stunting, and the freedom to use social media Instagram makes the @cegahstunting account an effective educational medium.